Mitochondrial regulation of cell cycle progression during development as revealed by the tenured mutation revealed in Drosophila. - Mandal, S.; Guptan, P.; Owusu-Ansah, E.; Banerjee, U. (Developmental Cell, 2005)
The precise control of the cell cycle requires regulation by many intrinsic and extrinsic factors. Whether the metabolic status of the cell exerts a direct control over cell cycle checkpoints is not well understood. We isolated a mutation, tenured (tend), in a gene encoding cytochrome oxidase subunit Va. This mutation causes a drop in intracellular ATP to levels sufficient to maintain cell survival, growth, and differentiation, but not to enable progression through the cell cycle. Analysis of this gene in vivo and in cell lines shows that a specific pathway involving AMPK and p53 is activated that causes elimination of Cyclin E, resulting in cell cycle arrest. We demonstrate that in multiple tissues the mitochondrion has a direct and specific role in enforcing a G1-S cell cycle checkpoint during periods of energy deprivation.